Stoicism and Frankfurtian Compatibilism - László Bernáth (Elpis)
Although the free will debate of contemporary analytic philosophy lacks almost any kind of historical perspective, some scholars (for instance Zimmerman 2000; Salles 2001, 2005) have pointed out a striking similarity between Stoic approaches to free will and Frankfurt’s well-known hierarchical theory (Frankfurt 1969, 1971, 1988). However, the scholarly agreement is only apparent because they disagree about the way of similarity between the Stoic and the Frankfurtian theories. The main thesis of my paper is that commentators have so far missed the crucial difference between the Stoics’ approach to free will and Frankfurt’s, a difference that renders the former as the superior theory. I make three main claims. In the first section, I argue that it is misleading and ultimately false to say that Frankfurt’s and the Stoics’ conception of free will are the same or notably similar to each other (pace Zimmerman 2000). Nevertheless, in the second section I show that there is indeed a relevant similarity between the two approaches. Both of them provide a semi-compatibilist reason- and reflectivity-based theory of moral responsibility. Finally, in the third section, I describe the difference that I take to be the most relevant between these theories regarding the problem of moral responsibility. I consider this difference as a crucial one because a serious disadvantage of the Frankfurtian view follows therefrom.